Benefits. Can we talk about them in the use of the electronic media as a consequence of SARS-COV-2? - Suárez-Rivero, David (2020)
In this paper I show that as a consequence of SARS-CoV-2 there have been not just damages but also benefits, namely: the increase of trust and responsibility by the citizens on the electronic media, and the opportunity that it has given to the human beings of continuing their social, emotional and working life. Particularly, I support that, although the electronic media has been used in some occasions to misinform, create fear and control in the population, they might be used differently, promoting with them trusted information, responsibility and establishing beneficial relationships.